Racang Bangun Sistem Pembayaran Parkir Otomatis Menggunakan Radio Frequency Identification Berbasis Internet of Things Studi Kasus STT Indonesia Tanjungpinang - Dedy Jauhari; Aurora Elsa Frederick; N. Supriyadi; Lisken Sirait; Alfan Fedrianto (LPPM STMIK Bandung, 2024)
Parking is a mandatory service in public places. Parking services have an important role, especially so that vehicles are neatly arranged. An organized and neat parking system will make vehicle users comfortable. However, if the parking system is not managed properly, it creates a major problem, namely making vehicles pile up and making vehicle users uncomfortable. Based on this, the author makes an automatic parking system using an internet of things-based RFID. By using the NodeMCU ESP8266 as a device controller as well as sending data to a database which will later be displayed on the web. To enter (input) this tool uses an RFID Scanner which is useful as a system control center that has the function of reading a unique code from the RFID tag. Then the Infrared Sensor which has a function to detect objects or in this case vehicles. For output (output) this tool uses a servo that is useful as a driver of the parking doorstop. Then there is the DFplayer which converts electrical signals into sound, the DFplayer here becomes a marker if there are vehicle users who have not been registered in the parking member and a marker if the parking lot is full. Based on these tests, it can be concluded that the automatic payment parking system using IOT-based RFID (Internet Of Things) requires an RFID Scanner, RFID tag/EKTP, IR Sensor, Servo, DFplayer, and NodeMCU 8266. And also requires a monitoring system that functions to regulate availability of parking space.